Respuesta del cultivo de maíz (Zea mays L.), sembrado con labranza mínima en diferentes densidades poblacionales en la zona de Babahoyo - López Veloz, Marco José (2013)
In the world is sown annually, approximately 129.2 million hectares of corn production reached around 477.4 million metric ton world. In Ecuador maize is the second most important grain for human consumption after rice, where it employed about 40,000 people who are 11% of the economically active population engaged in agriculture, our country currently planted 320,000 hectares about its production being distributed, 60% in the Guayas, Los Ríos, El Oro and Loja (about 20,000 ha). The objective of this research was to determine the behavior of maize hybrids in different planting densities under minimum tillage with chemical fertilization program to evaluate their effect on performance. The work was conducted in the experimental farm land "San Pablo", located on 7.5 km of track Babahoyo-Montalvo. We investigated maize hybrids DK-7088, Pioneer 30S0 and Gladiator, with 4 subtratamientos in plots of 30 m2, distributed in a design of randomized complete block split plot. For the evaluation of means used the Tukey test at 5% probability. During the crop cycle were evaluated: plant height, ear diameter, number of ears per plant, ear length, days to harvest, days to flowering, seed weight, yield per hectare and an economic analysis of the treatments